Synergistic effect of resveratrol and HSV-TK/GCV therapy on murine hepatoma cells. Issue 2 (1st February 2019) - Xiao, Jianyong; Wang, Xiaolan; Wu, Yingya; Zhao, Qing; Liu, Xiaodong; Zhang, Guangxian; Zhao, Zengqiang; Ning, Yizhen; Wang, Kun; Tan, Yuhui; Du, Biaoyan
ABSTRACT: Despite its low transfer efficiency, suicide gene therapy with HSV-TK is known for its bystander killing effect. The connexin-based gap junction is believed to mediate the bystander effect. Recently, we found that resveratrol, a polyphenol compound, increased the expression of Cx26 and Cx43, which are connexins and important constituents of gap junctions, in murine hepatoma cells. Hypothetically, the resveratrol-induced upregulation of gap junctions may improve the bystander effect that HSV-TK/GCV has on hepatoma cells. Our present investigation revealed that resveratrol could enhance intercellular communication at the gap junctions in CBRH7919 hepatoma cells and thereby enhance the bystander killing effect of GCV on CBRH7919 TK cells. However, inhibition of gap junction using its long-term inhibitor alpha-glycyrrhetinic acid had a negative influence on the bystander effect of gene therapy with HSV-TK/GCV. In addition, combined resveratrol and GCV treatment in tumor-bearing mice with CBRH7919 TK and CBRH7919 WT cells at a ratio of 2:3 resulted in a significant decrease in the volume and weight of the tumor in comparison to GCV or only resveratrol. The present results demonstrate that resveratrol can enhance the bystander effect exerted by the HSV-TK/GCV system by enhancing connexin-mediated gap junctional communication.